Molecular profiling and identification of prognostic factors in Chinese patients with small bowel adenocarcinoma. Issue 11 (12th September 2021) - Pan, Hongming; Cheng, Huanqing; Wang, Huina; Ge, Weiting; Yuan, Meiqin; Jiang, Sujing; Wan, Xiangbo; Dong, Ying; Liu, Zhen; Zhao, Rongjie; Fang, Yong; Lou, Feng; et al.
Abstract: Small bowel adenocarcinoma (SBA) is a rare malignancy with a poor prognosis and limited treatment options. Despite prior studies, molecular characterization of this disease is not well defined, and little is known regarding Chinese SBA patients. In this study, we conducted multigene next‐generation sequencing and 16S ribosomal RNA gene sequencing on samples from 76 Chinese patients with surgically resected primary SBA. Compared with colorectal cancer and Western SBA cohorts, a distinctive genomic profile was revealed in Chinese SBA cohorts. According to the levels of clinical actionability to targetable alterations stratified by OncoKB system, 75% of patients harbored targetable alterations, of which ERBB2, BRCA1/2, and C‐KIT mutations were the most common targets of highest‐level actionable alterations. In DNA mismatch repair–proficient (pMMR) patients, significant associations between high tumor mutational burden and specific genetic alterations were identified. Moreover, KRAS mutations/ TP53 wild‐type/nondisruptive mutations ( KRAS mut /TP53 wt/non‐dis ) were independently associated with an inferior recurrence‐free survival (hazard ratio [HR] = 4.21, 95% confidence interval [CI] = 1.94‐9.14, P  < .001). The bacterial profile revealed Proteobacteia, Actinobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Cyanobacteria were the most common phyla in SBA. Furthermore, patients were clustered into three subgroups based on the relative abundance of bacterial phyla, and the distributions of the subgroups were significantly associated with the risk of recurrence stratified by TP53 and KRAS mutations. In conclusion, these findings provided a comprehensive molecular basis for understanding SBA, which will be of great significance in improving the treatment strategies and clinical management of this population. Abstract : Molecular characterization of small bowel adenocarcinoma (SBA) is not well defined, and little is known regarding Chinese SBA patients. Compared with colorectal cancer and Western SBA cohorts, a distinctive genomic profile was revealed in Chinese SBA cohorts. A molecular subtype of KRAS mutations/TP53 wild‐type/nondisruptive mutations was found to be associated with an inferior recurrence‐free survival in SBA.